Anti-stigmatizing: a collaborative autoethnography on recovery from depression - Zhu, Danlei; Lyu, Keyi (Frontiers in Psychiatry, 2024)
Introduction: Despite extensive research on clinical treatments for depression, there remains a significant gap in understanding of the lived experiences and recovery journeys of those with depression. This study sought to explore the recovery process through an "anti-stigmatizing" lens, emphasizing the cultural-psychological mechanisms at play and the importance of personal narratives in shaping the recovery trajectory.Methods: Using a collaborative autoethnographic approach, this report focuses on the first author's journey of depression recovery. This research methodology allows for an in-depth exploration of subjective experiences, with a specific emphasis on the interaction between societal stigma, personal identity, and mental-health challenges.Results: It is found that the depression-recovery experience can be divided into four stages from an anti-stigma perspective: (1) encountering the public stigma of emotions; (2) internalizing the stigma to a self-stigma; (3) "decriminalizing" the expected stigma of a "depressed" identity through diagnosis; and (4) being able to cope with and understanding the public stigma relating to depression when facing it again. Key factors that were found to contribute to recovery were self-awareness, community empowerment, and recognition and acceptance by close friends and family.We propose a reconceptualization of depression that incorporates a societal perspective on internalized stigma. Recovery from depression is not merely a medical process; it also pertains to how the patient frees themselves from public stigma. The results strongly indicate the need for a paradigm shift toward a more inclusive and empathetic approach to mental-health care, and we emphasize the importance of personal narratives in depression recovery.